Revitalization of Qur'anic Based Islamic Education: An Implementative Study of Surah An-Nahl Verse 125 as a Teaching Method - Firdaus, Muhammad; Ruslan, Ruslan; Muslimin, Muslimin (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
The revitalization of Quran-based Islamic education has become an urgent need in facing the moral crisis and spiritual challenges of the current generation. Islamic education is not merely about transferring knowledge but also about shaping noble character and a personality oriented toward divine values. This study aims to analyze the implementation of Surah an-Nahl verse 125 as a teaching method at the Darul Hikmah Islamic Boarding School in Bima City. This verse contains educational principles through the approaches of hikmah (wisdom), mau'izhah hasanah (good advice), and jidal billati hiya ahsan (wise dialogue), which can be used as pedagogical guidelines in shaping the character of students. This study uses a qualitative approach with observation, in-depth interviews, and documentation of learning activities. The results indicate that the values of Qur’an surah an-Nahl verse 125 have been internalized in the educational process, evident from teaching practices that emphasize the strengthening of morals, tolerance, communication ethics, and balanced religious awareness. The implications of these findings affirm that a Qur'an-based approach can be effectively applied in the context of pesantren education. This revitalization encourages the development of teaching methods that address cognitive, affective, and spiritual dimensions in an integrated manner.